The survival guide to Auslan : a beginner's pocket dictionary of Australian Sign Language - Fahey, Shaun; Johnston, Trevor; Schembri, Adam; Royal Institute for Deaf and Blind Children, Sydney (Victoria : Deaf Australia Inc., 2018)
Mini woordenboek Auslan, de Australische gebarentaal.